Understanding metal concentration and speciation in motorway runoff. Issue 11 (12th May 2022) - Zakharova, Julia; Pouran, Hamid; Bridgeman, John; Wheatley, Andrew; Arif, Mohammed
ABSTRACT: Although highway runoff has historically been extensively studied, the increasing complexity of stormwater management means that there are still significant gaps regarding the reduction of soluble metals. The work reported in this paper addresses these challenges by analysing the presence and behaviour of iron, copper and zinc in runoff from junction 24 of the M1 motorway in the UK (peak traffic flow: 30, 000 vehicles per hour) and comparing it with other urban sources of metals found in the same catchment (a local brook and sewage treatment works). The sampling site included an interceptor and a treatment lagoon and the event monitoring indicated a trend by which the metals did not change their concentration or particulate soluble proportion immediately, hence showing that pre- and post-storm conditions are important factors when analysing the solubility of metals and their behaviour. The data provided further evidence of the important influence of storm characteristics on metal concentrations in highway runoff, in particular the effects of an antecedent dry weather period (ADWP). In addition, this study also helped us to better understand how the release of sodium the application of de-icer for road maintenance in winter affects the availability of zinc. GRAPHICAL ABSTRACT: UF0001